Therapeutic potency of bee pollen against biochemical autistic features induced through acute and sub-acute neurotoxicity of orally administered propionic acid. Issue 1 (December 2016) - Al-Salem, Huda; Bhat, Ramesa; Al-Ayadhi, Laila; El-Ansary, Afaf
Abstract Background It is now well documented that postnatal exposure to certain chemicals has been reported to increase the risk of autism spectrum disorder. Propionic acid (PA), as a metabolic product of gut microbiotaandas a commonly used food additive, has been reported to mediate the effects of autism. Results from animal studies may help to identify environmental neurotoxic agents and drugs that can ameliorate neurotoxicity and may thereby aid in the treatment of autism. The present study investigated the ameliorative effects of natural bee pollen against acute and sub-acute brain intoxication induced by (PA) in rats. Methods Twenty-four young male Western Albino ratswere enrolled in the present study. They were classified into four equal groups, eachwith6 rats. The control group received only phosphate buffered saline; the oral buffered PA-treated groups (II and III) received a neurotoxic dose of 750 mg/kg body weight divided in 3 dose of 250 mg/kg body weight/day serving asthe acute group and 750 mg/kg body weight divided in 10 equal dose of 75 mg/kg body weight/day as the sub-acute group. The fourth group received 50 mg bee pollen for 30 days after PA-acute intoxication. Results The obtained data showed that the PA-treated groups demonstrated multiple signs of brain toxicity, as indicated by a depletion of serotonin (5HT), dopamine and nor-adrenaline, together withan increase in IFN-γ and caspase 3. Bee pollen was effective in ameliorating the neurotoxic effect of PA. All measured parameters demonstrated minimal alteration in comparison with thecontrol animal than did those of acute and sub-acute PA-treated animals. Conclusions In conclusion, bee pollen demonstrates anti-inflammatory and anti-apoptotic effects while ameliorating the impaired neurochemistry of PA-intoxicated rats.